Multi-objective optimization of vertical and horizontal solar shading in residential buildings to increase power output while reducing yearly electricity usage (2025)
Background: One of the effective strategies to reduce residential energy use is shading devices. Shading devices can be installed adjacent to windows in vertical or horizontal orientations to regulate the amount of sunlight entering a building. This study focuses on Photovoltaic Shading Devices (PVSDs), which combine traditional shading functions with photovoltaic (PV) technology. PVSDs are designed to block excessive sunlight and convert incident solar radiation into electricity, thereby serving dual purposes of energy conservation and renewable energy production. Methodology: This work presents a multi-objective optimization of PVSD configurations to maximize power output and reduce annual electricity consumption in residential buildings. Nine design variables were optimized using EnergyPlus software for energy simulation and JEPLUS + EA software for optimization. The study analyzed four cities representing different climate types. Results: The results showed that the use of solar shading for the city of Bandar Abbas reduces electricity consumption by 1000 kWh per year and also produces 1920 kWh of electricity. In the south, west, north, and east directions, electricity has improved between 15 and 37 %, 10–29 %, 7–22 %, and 7–30 % annually. The findings highlight the effectiveness of PVSDs in balancing energy efficiency and renewable energy production, with significant variations depending on climate and building orientation.